Neurovascular Surgery Surgical Approaches for Neurovascular Diseases - July, Julius; Wahjoepramono, Eka J.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Springer, 2019)
This open access book presents the diagnosis, investigation and treatment of neurovascular diseases, and offers expert opinions and advice on avoiding complications in neurovascular surgery. It also covers complication management and post-operative follow-up care. The book is divided in to three parts; the first part discusses common approaches in neurovascular surgery, describing the steps, indications for and limitations of the approach, as well as the associated complications and how to avoid them. The second part addresses surgical treatment based on pathology, taking the different locations of lesions into consideration. The third part focuses on the technological developments that support neurovascular surgery, which may not be available everywhere, but have been included to help vascular surgeon understand the principles. This book is a guide for young neurosurgeons, neurosurgery residents and neurosurgery fellows, as well as for medical students and nurses who are interested in neurosurgery or are associated with this field in any way. It is also a useful teaching aid for senior neurosurgeons.
Pterional approach for neurovascular surgery -- Eyebrow keyhole approach for neurovascular surgery.-Fronto-orbito-zygomatic (FOZ) approach for neurovascular surgery.-Lateral supraorbital approach for neurovascular surgery -- Interhemispheric approach for neurovascular surgery -- Subtemporal approach for neurovascular surgery -- Lateral suboccipital approach for neurovascular surgery.-Transmastoid approach for neurovascular surgery -- Middle fossa approach for neurovascular surgery -- Basic endovascular technique for neurovascular surgery -- Surgery of posterior communicating artery aneurysm -- Surgery of IC-Anterior choroidal aneurysms -- Surgery of paraclinoid aneurysm -- Surgery of anterior communicating artery aneurysms -- Surgery of middle cerebral artery (MCA) Aneurysm -- Surgery of posterior cerebral artery aneurysm -- Surgery of upper basilar aneurysm -- Surgery of superior cerebellar artery aneurysm -- Surgery of posterior inferior cerebellar artery (PICA) aneurysms -- Surgery of giant aneurysm -- Surgery of posterior fossa AVM -- Endovascular coiling of intracranial aneurysms -- Neuroendoscopic surgery for intracerebral hematomas using a transparent sheath -- Surgery of intracerebral hemorrhage -- Intracranial dural arteriovenous fistula: Microneurosurgery basics and tricks -- Moyamoya disease basic concepts of diagnostics and treatment -- Adenosine in complex aneurysm surgery -- Spinal arteriovenous malformations -- Vasospasm following aneurysmal subarachnoid hemorrhage -- Retractorless surgery of vascular lesions -- FLOW 800 for vascular surgery -- Gamma knife surgery for atrio venous malformations.
Keywords: Nervous system$1 (BSurgery.s; Blood-vessels$1 (BSurgery.s; Neurosurgery; Vascular Surgery